Merulempista turturella (Zeller, 1848) new to the Maltese Islands (Lepidoptera: Pyralidae, Phycitinae) - Agius, Jonathan (SHILAP Revista de lepidopterología, 2024)
The genus Merulempista Roesler, 1967 and the species Merulempista turturella (Zeller, 1848) are reported for the first time from the Maltese Islands. Distribution and habits of the larvae and adult are included. A Maltese name is proposed for this new record.